Mercado de trabajo y género durante el siglo XX. Un análisis sobre las causas de la feminización de la política asistencial en Argentina - Brenda Brown; Noemí Giosa Zuazúa; Corina Rodríguez Enríquez (Revista de Estudios Sociales, 2024)
This article delves into the intricate relationship between the evolution of Argentina’s labor market, particularly the historical inclusion of women, and the contours of contemporary social welfare policies for female recipients. Set against the backdrop of a decades-long crisis in employment and income, especially affecting low-income families and women tasked with caregiving responsibilities, the article posits the hypothesis that the trend of feminization in social welfare policies partly stems from the pauperization of Argentina’s labor market in the latter part of the 20th century and the historically subordinate role of women within patriarchal capitalist societies. Employing an empirical-historical methodology, it scrutinizes the shifts and dynamics of the labor market over the 20th century as well as the features of the welfare policy framework at the beginning of the 21st century. The article is a contribution to Argentina’s labor market and social policy literature and portrays current socio-welfare programs as an adaptation to the employment and income crisis, further entrenching women’s subordinate status within the social fabric.